LA PURíSIMA VOLCANIC FIELD, BAJA CALIFORNIA SUR (MEXICO): MIOCENE TO QUATERNARY VOLCANISM RELATED TO SUBDUCTION AND OPENING OF AN ASTHENOSPHERIC WINDOW - Bellon H.; Aguillón-Robles A.; Calmus T.; Maury R.C.; Bourgois J.; Cotten J. (My University, 2006)
Geological mapping and geochemical analyses combined with 40K-40Ar ages for lavas from the Late Miocene to Quaternary La Purísima volcanic field (Baja California Sur) provide evidence for five volcanic events. These, in turn, may reflect plate interactions in the region. The oldest event (event 1), prior to 11 Ma, corresponds to the emission of normal to K-rich calc-alkaline lavas, exposed as large mesas in the eastern part of the studied area and as pyroclastic breccias and volcaniclastic sediments to the west. It is associated with the end of the Comondú arc activity resulting from subduction of the Farallon and Guadalupe plates. Between 10.6 and 8.8 Ma (event 2), magnesian andesites and tholeiites were emplaced. At 5.5 Ma (event 3) and 2.5 Ma (event 4) small volumes of magnesian andesites erupted in the central and southern parts of the volcanic field. Finally, between 1.2 Ma and Holocene (event 5), numerous basaltic and magnesian andesitic fissural and central emissions resulted in the formation of strombolian cones and associated lava flows, mainly distributed within a NNW-SSE trending graben located SE of the town of La Purísima. Magmatic events 2 to 5 occurred well after the supposed end of the subduction event. Their geochemical characteristics are still typical of subduction-modified sources and possibly indicate partial melting of hot slab and formation of an asthenospheric window due to a slab rupture event which followed ridge-trench collision, prior to the continental breakup of the Gulf of California extensional province. © 2005 Elsevier B.V. All rights reserved.
Keywords: ASTHENOSPHERIC WINDOW; BAJA CALIFORNIA SUR (MEXICO); K-AR AGES, LATE MIOCENE TO QUATERNARY VOLCANISM; MAGNESIAN ANDESITES, THOLEIITES; SUBDUCTION; Holocene; Miocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен